The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/gps.1854
|View full text |Cite
|
Sign up to set email alerts
|

Adjunct extended‐release valproate semisodium in late life schizophrenia

Abstract: While extended-release valproate semisodium appears efficacious and well tolerated in older adults with schizophrenia, data from larger, controlled trials is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…A total of 38 articles reached the screening stage, of which 3 were excluded because of demographic research, 44 46 1 which was irrelevant to schizophrenia 47 and 1 which did not include a direct comparison of valproate augmentation therapy, 11 , 48 , because they were nonclinical trials such as case report/series, comments, or review articles, 22 , 36 , 49 57 1 because it used retrospective data, 58 4 because of a lack of detailed data on treatment effect, 12 , 35 , 59 , 60 and 6 because of a lack of a control group. 29 , 61 – 65 After the screening procedure, a total of 11 articles remained for the current meta-analysis (Table 1 ). 8 , 25 27 , 30 – 34 , 37 , 66 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 38 articles reached the screening stage, of which 3 were excluded because of demographic research, 44 46 1 which was irrelevant to schizophrenia 47 and 1 which did not include a direct comparison of valproate augmentation therapy, 11 , 48 , because they were nonclinical trials such as case report/series, comments, or review articles, 22 , 36 , 49 57 1 because it used retrospective data, 58 4 because of a lack of detailed data on treatment effect, 12 , 35 , 59 , 60 and 6 because of a lack of a control group. 29 , 61 – 65 After the screening procedure, a total of 11 articles remained for the current meta-analysis (Table 1 ). 8 , 25 27 , 30 – 34 , 37 , 66 …”
Section: Resultsmentioning
confidence: 99%
“…The duration of adding divalproex sodium for schizophrenia treatment is also different. Some research has argued that treatment was only seen as significant from the beginning of the administration to the second, third, and fourth weeks, while there are also studies reporting the benefits until the 12th week with no significant change thereafter (23)(24)(25)(26)(27)(28). Other studies showed no significant improvement at the end of the study and more benefits were seen at the beginning of the addition of divalproex sodium especially for the improvement of positive symptoms when compared to those who were not treated with Divalproex sodium (29).…”
Section: Discussionmentioning
confidence: 99%
“…Their outcomes showed psychosis scores calculated by positive and negative syndrome scale (PANSS), global functioning as tested by global assessment scale (GAS), and depression, as measured by geriatric depression scale (GDS), to be significantly reduced in the patients. Thus, they concluded that an extended-release of VPA in older schizophrenia patients appeared to be effective and well-tolerated [168].…”
Section: Vpa Treatment In Schizophrenia Human Studiesmentioning
confidence: 98%